Success Factors for Smart City in Urban Design Models: A Systematic Review - Martiana Kholila Fadhil; Tony Dwi Susanto (School of Computing, Telkom University, 2023)
Sustainable urban development cannot be separated from the smart city concept which can solve the problems of urban areas in recent years. The purpose of this study is to review literature studies on creating Urban Design models that influence the successful implementation of Smart City in urban areas toward sustainable urban development. Sustainable urban development in the Smart City concept is not limited to solutions using IT-based technology but needs to pay attention to solutions to the physical condition of cities due to the increase and decrease in the number of residents in urban areas. From this context, this research agrees on models, concepts, and indicators to measure the success factors of smart cities in Indonesia. This research method was carried out by studying the literature used derived from various articles filtered into 40 articles about urban design in Smart City. The result of this study is a systematic literature review consisting of 3 domains, 8 aspects and 40 indicators of Urban Design influencing the success of Smart City in the local government. The results of this study can contribute to the implementation of the Urban Design model in sustainable urban development.